PERADILAN AGAMA DI INDONESIA - Ahmad R (Program Studi Hukum Keluarga Islam, 2015)
Religious Court in Indonesia has a long history in accordance with the history of Islam in Indonesia. This article portrays the development of religious court on Indonesia since the era of Islamic kingdom until the New Order era.